(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Recent decades are characterized by the large-scale introduction of Information Technology in various spheres of human life. Allows the implementation and use of intellectual transport systems to ensure road safety and solve the problem of improving road condition. Typically they are a set of interconnected functional systems, such as data collection systems from automotive detectors and television cameras. Due to the variety of external conditions under which these systems should work, the methods used in their creation can be very different from each other. However, most of the systems available today have two main blocks: the system of image acquisition and its subsequent analysis, the results of which are largely determined by the quality of the images obtained.